Analysis of Factors Affecting the Integrity of Financial Reports in Banking Sector Companies - I Gede Cahyadi Putra; Ida Ayu Ratih Manuari; Putu Ayu Diah Widari Putri; Ni Ketut Emayanti; Ni Kadek Vina Angelica Putri (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
Financial statement integrity refers to financial statements that accurately reflect the true condition of a company, without anything being concealed or hidden. The importance of financial statement integrity has become an increasingly pressing requirement that companies must fulfill in order to avoid misleading financial statement users, which could result in erroneous decision-making. This study aims to analyze the influence of managerial ownership, institutional ownership, company size, financial distress, and leverage on financial statement integrity in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The research population consists of banking sector companies listed on the IDX during the 2021-2023 period. This study involves 20 companies selected as samples using purposive sampling. The analysis technique used to test the hypotheses is multiple linear regression analysis. The results of this study indicate that managerial ownership, institutional ownership, company size, and leverage do not affect financial statement integrity, while financial distress has a negative effect on financial statement integrity. This study is expected to provide general input to managers or strategists at companies listed on the Indonesia Stock Exchange to always align all interests involved in company management.